Encounters by the rivers of Babylon - Gabbay, Uri; Secunda, Shai (Texte und Studien zum antiken Judentum ;, 2014)
This volume presents a group of articles that deal with connections between ancient Babylonian, Iranian and Jewish communities in Mesopotamia under Neo-Babylonian, Achaemenid, and Sasanian rule. The studies, written by leading scholars in the fields of Assyriology, Iranian studies and Jewish studies, examine various modes of cultural connections between these societies, such as historical, social, legal, and exegetical intersections. The various Mesopotamian connections, often neglected in the study of ancient Judaism, are the focus of this truly interdisciplinary collection. Reihe Texts and.